Ubi Jalar Sebagai Salah Satu Alternatif Pengembangan Produk Snack - Ani Nuraeni; Thalita Fauziah (IPB University, 2016)
The general purpose of product development of snack made from sweet potato. Product development is very important thing to do to make consumers do not feel bored with product that already on the market and make a product with better quality and benefits. Product development has a purpose to improve and complete the product that already exist. The product that will be developed is a snack from sweet potato. Snack from sweet potato has not been a common in the market. This product development has been done to inform the society that the food from sweet potato can be a very delicious and nutritious snack. Sweet potato was chosen because it is easy to find with inexpensive price, easy to process, have good nutrition for body, and have a longer shelf life.